Measurement of the Physical Properties during Laparoscopic Surgery Performed on Pigs by Using Forceps with Pressure Sensors - Hiroyuki Yamanaka; Kazuhide Makiyama; Kimito Osaka; Manabu Nagasaka; Masato Ogata; Takahiro Yamada; Yoshinobu Kubota (Advances in Urology)
Objectives. Here we developed a unique training system, a patient specific virtual reality simulator, for laparoscopic renal surgery. To develop the simulator, it was important to first identify the physical properties of the organ. Methods. We recorded the force measured during laparoscopic surgery performed on pigs by using forceps with pressure sensors. Several sensors, including strain gauges, accelerometers, and a potentiometer, are attached to the forceps. Results. Throughout the experiment, we measured the reaction force in response to the forceps movement in real time. Conclusions. The experiment showed the possibility of digitizing these physical properties in humans as well.